Is it more effective group relaxation than individual to reduce anxiety in specific phobias? - Julián Carretero Román (Fundación para el Desarrollo de la Enfermería, 2009)
Relaxation is a standard technique used by nurses to reduce the level of anxiety. It seems that their implementation on a group can bring certain benefits compared with individual relaxation. This outline is intended to raise this hypothesis in caring for individuals diagnosed with specific phobia, by approaching the problem from the cognitive behavioural therapy perspective. In addition, it seeks to evaluate the usefulness of the nurse intervention relaxation to reduce the level of anxiety, in turn comparing the results obtained using an indicator of the scale of results NOC and the Hamilton Anxiety Scale. The phobia is a specific entity underdiagnosed, whose prevalence is about 10%. Those affected can live a really limited and debilitating, deteriorating quality of life. The community mental health nurses are in a unique position to participate in the cognitive behavioural therapy through relaxation, which will allow them to reduce the level of anxiety when people establish contact with the phobic stimulus. Methodology: quasi-experimental study in specific phobia diagnosed, 20 to 40 years old adults attending for the first time to the mental health facility derived from primary care. Both the control group as the pilot will be treated by conducted cognitive-behavioural psychotherapy individualized according to the therapeutic protocol MSC, except in terms of relaxation, which in the experimental group will be conducted at the group level. The effectiveness of treatment will be assessed with the Hamilton anxiety scale and the likert type scale of outcome indicators NOC "stress level" with 3 measurements, before starting, immediately after completing the sessions of relaxation and three months later, checking the decline in the average level of anxiety.